PERCEPTION OF DEVELOPING DIGITAL MARKETING STRATEGIES FOR COMMUNITY-BASED TOURISM IN KOH KRET, NONTHABURI PROVINCE - Saesong ๋Jong; ThodThankhun , Thanu; Satientanasan, Suppachat (Journal of Liberal Art of Rajamangala University of Technology Suvarnabhumi, 2025)
This research aimed to 1) study the perception of tourism potential for digital marketing development of Koh Kret community 2) study the perception of factors affecting digital marketing of Koh Kret community and 3) study the perception of propose a guideline for the development of digital marketing for tourism in Koh Kret community by using mixed research. The sample for Quantitative research consisted of 400 tourists chosen by simple sampling. The research instrument was a satisfaction assessment form. The statistics used were percentage, mean, and standard deviation. Qualitative research had the key informants as 10 local experts, 10 community leaders, 20 farmers and occupational groups, 10 citizens, and 5 government agencies. The tools used were indepth interviews, focus group discussions, and large group meetings. The quantitative research results found that: Perceived tourism potential Accessibility = 4.219, Attractiveness = 4.068, Activities = 3.748, Perceived online marketing mix factors, Products = 3.58, Price = 4.14 and Personal service = 3.28. The qualitative research results found that Koh Kret has the potential to access, has attractions, accommodations, facilities, and activities as strengths, has tangible products that meet the needs of buyers on social media, maintains privacy and good value for money, has communication on social media such as TikTok, Facebook pages to creates relationships between products and buyers, creates loyalty to products that saves long-term costs in purchasing products as well as be trustworthy and also has a website that is ranked quickly on search engines to increases brand awareness and sales on attraction marketing that is good value for money and sustainability and become known to tourists.